FACTORS AFFECTING THE ADOPTION OF ELECTRONIC MONEY USING TECHNOLOGY ACCEPTANCE MODEL AND THEORY OF PLANNED BEHAVIOR - Filona Filona; Misdiyono Misdiyono (Universitas Gunadarma, 2019)
With the rapid growth of information technology, electronic money has played an important and central role in the e-payment. Development of electronic money is able to create a trend less-cash society, which is a society’s behavior using non- cash transactions by utilizing the simplicity offered through electronic transactions. The purpose of this research is to determine the factors affecting the intention to use electronic money. We designed a questionnaire and used it to survey a simple random sampling of people who use of e-money in DKI Jakarta. The actual samples used for the study are 125 respondents. We analyzed the data using Structured Equation Modeling to evaluate the strength of the hypothesized effects. The result of the analysis showed that perceived ease of use has no significant effect on attitudes towards the use of e-money. Perceived ease of use has a significant effect on the perceived usefulness of e-money. Perceived usefulness has no significant effect on the intention to use e-money. Perceived usefulness has a significant effect on attitudes towards the use of e-money. Attitude has a significant effect on the intention to use e-money. Subjective norm has a significant effect on the intention to use e-money. Perceived behavioral control has no significant effect on the intention to use e-money.